ETIOLOGICAL ASSESSMENT OF OUR CHRONIC LOW BACK PAIN PATIENTS - Ali Gür; Kemal Nas; Remzi Çevik; Ferda Erdoğan; A. Jale Saraç (Archives of Rheumatology, 2000)
Low back pain is an extremely common condition, affecting 80% of individuals at some point in their lifetime. Most episodes of acute low back pain resolve spontaneously, regardless of the type of therapy chosen. However, a small percentage of these acute cases, 5-10% in most series, progress to develop chronic low back pain. Epidemiologic studies have established demographic characteristics and risk factors for the development of low back pain. This study was carried out on 312 cases refering to the Universıty of Dicle, Faculty of Medicine, Physical Medicine and Rehabilitation department with chronic low back pain. The patients were classified according to etiology, age, sex, profession, duration and localization of pain, clinical and radiological findings.